Effect of ionic liquids modified nano-TiO2 as additive on tribological properties of silicone grease. (26th October 2021) - Wu, Lining; Xia, Yanqiu; Xiong, Shenzhan; Wu, Hao; Chen, Zhongshan
Abstract: A series of silicon greases were fabricated by using polytetrafluoroethylene as thickening agent and polydimethylsiloxane as base oil. Four kinds of ionic liquids modified nano-titanium dioxide were employed as solid additives with different concentrations of 0.5, 1.0, 1.5, 2.0, 2.5 and 3.0 wt%. The chemical composition and thermal stability of the additives were explored by a Fourier transform infrared spectroscopy and a thermal gravimetric analyzer at a heating rate of 10 °C min −1 under a flow of nitrogen, respectively. The volume resistivity of greases was measured by a volume surface resistance tester in the room temperature of 25 °C. The tribological properties were investigated using a ball-on-disc tribometer under a stroke of 5 mm, a frequency of 5 Hz and different applied loads of 50, 100, 150 and 200 N. After tribological tests, a scanning electron microscopy and x-ray photoelectron spectroscopy were used to probe the lubrication mechanisms. Results showed that nano-titanium dioxide were successfully modified by ionic liquids and their decomposition temperatures were all higher than 300 °C. Meanwhile, the addition of additives had a significant influence on the conductivity and tribological properties of the greases. Specially, the grease containing 1.5 wt% additives exhibited good friction reduction and anti-wear abilities. The analysis of the worn surfaces indicated that the reasons for raising the anti-friction and anti-wear abilities were attributed to the synergistic effects of ionic liquids and solid additives which promoted the formation of lubricating films on the worn surfaces.